CONMEBOL libertadores cup: altitude impact on goals and results in 16 years of soccer matches - Cabrera-Hernández, M. A.; García-Corzo, S. A.; Povea-Combariza, C. E.; Tafur-Tascón, L. J.; Hurtado, H.; Tovar-Cuevas, J. R.; Mosquera-Miranda, C. A.; Grijalba-González, D. F. (Journal of Human Sport & Exercise, 2023)
Background: The CONMEBOL Libertadores Cup, is the continent`s most important international club tournament. Teams are exposed to different altitudes with short acclimatization periods. The present study describe the effect of altitude on the results and goals of soccer club teams matches between 2000 and 2015 in the CONMEBOL Libertadores Cup.